2019
DOI: 10.1111/ijsa.12260
|View full text |Cite
|
Sign up to set email alerts
|

Why does impression management positively influence interview ratings? The mediating role of competence and warmth

Abstract: Though interviews assess job applicants' skills and abilities, they can be influenced by extraneous factors, including impression management (IM) tactics. Interviewees’ self‐promotion and ingratiation IM tactics predict higher interview ratings; however, researchers have yet to determine why these tactics work. We assessed whether two fundamental dimensions of social perception, competence and warmth, mediate the relationship between IM tactics and interview ratings. We hypothesized that interviewee competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…This is in line with results from Jansen et al () who found that applicants primarily used those faking and IM tactics that are expected by interviewers, such as honest self‐promotion. More generally, evidence suggests that applicants engage in more honest IM than in faking (Amaral, Powell, & Ho, ; Bourdage et al, ).…”
Section: How Common Is Faking In Interviews?mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with results from Jansen et al () who found that applicants primarily used those faking and IM tactics that are expected by interviewers, such as honest self‐promotion. More generally, evidence suggests that applicants engage in more honest IM than in faking (Amaral, Powell, & Ho, ; Bourdage et al, ).…”
Section: How Common Is Faking In Interviews?mentioning
confidence: 99%
“…Even though some suggestions have been put forth to prefer alternative selection procedures to interviews because of the latter's potential for faking (Koenig et al, ), the extant research examining whether and how faking influences actual interview outcomes like interview performance ratings or interview success (e.g., receiving a job offer or an invitation for the next round of selection) reports mixed results (Table ). Studies that investigated relationships between self‐reported faking and outcomes in actual interviews found correlations that ranged from small and negative to null to moderate and positive (Amaral et al, ; Bourdage et al, , Study 5; Buehl & Melchers, , Study 1; Levashina & Campion, , Study 5; Roulin et al, ). Furthermore, four studies examined relationships between self‐reported faking and interview performance in mock interviews: two studies found small to moderate positive correlations (Buehl & Melchers, , Study 2; Ingold, Kleinmann, König, & Melchers, ) and two others found negative correlations (Bourdage et al, , Study 4; Swider et al, ).…”
Section: Does Faking In Interviews Matter?mentioning
confidence: 99%
“…The type of image that candidates try to create depends on what goals they are trying to achieve. Regardless of a candidate's specific goals, theory and empirical findings indicate that it is particularly important to be viewed as likeable/warm and competent (e.g., Amaral, Powell, & Ho, 2019;Ferris & Judge, 1991;Leary & Kowalski, 1990) and honest (Jansen et al, 2012;Jones & Pittman, 1982). Therefore, during the interview, self-presentation is often aimed at fostering these images.…”
Section: Self-presentation and Social Anxietymentioning
confidence: 99%
“…The data from the 2017 sample have been published, answering different research questions (seeAmaral, Powell, & Ho, 2019). Additional information is provided in the data transparency appendix in the supplementary materials.…”
mentioning
confidence: 99%
“…Ratings of interview performance have often been used as criteria against which to judge the effect of IM tactics. Research has found that the relationship between honest IM tactics and interview ratings is generally positive; whereas the relationship between deceptive IM tactics tends to be lower (Amaral et al, 2019; Bourdage et al., 2018; Kristof‐Brown et al, 2002; Melchers et al, 2020). It is likely that deceptive IM tactics are less related to interview performance ratings because they are difficult for interviewers to identify (Roulin et al, 2015), or that applicants use them less effectively.…”
Section: Introductionmentioning
confidence: 99%